1989
DOI: 10.1037/0882-7974.4.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal impact of interhousehold caregiving on adult children's mental health.

Abstract: The wear-and-tear hypothesis of caregiving (the longer care provided, the more psychological strain on caregivers) was examined using panel survey data from 112 adult children providing interhousehold care to an impaired elderly parent. Measures included subjective caregiving stress and perceived caregiving effectiveness ("wear") and depression and affect balance ("tear"). Contrary to the hypothesis, data revealed variability in children's adaptation to caregiving, improvement rather than deterioration being t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
152
3
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(173 citation statements)
references
References 19 publications
15
152
3
3
Order By: Relevance
“…The first states that both physical and psychological depletion should be expected for caregivers in the long term, as their -physical and psychological -resources get progressively exhausted (Johnson & Catalano, 1983). On the other hand, the later suggests that the familiar adjustment to the caregiver role improves over time (Townsend, Noelker, Deimling, & Bass, 1989), more in view with the actual resilience theories. That the arousal of psychiatric symptoms in a family system would better suit the wear and tear hypothesis, while ID carers would probably suit the adaptational theory.…”
Section: Discussionmentioning
confidence: 90%
“…The first states that both physical and psychological depletion should be expected for caregivers in the long term, as their -physical and psychological -resources get progressively exhausted (Johnson & Catalano, 1983). On the other hand, the later suggests that the familiar adjustment to the caregiver role improves over time (Townsend, Noelker, Deimling, & Bass, 1989), more in view with the actual resilience theories. That the arousal of psychiatric symptoms in a family system would better suit the wear and tear hypothesis, while ID carers would probably suit the adaptational theory.…”
Section: Discussionmentioning
confidence: 90%
“…Although the wear-and-tear hypothesis of caregiving (Townsend, Noelker, Deimling, & Bass, 1989) would suggest that the cumulative toll of providing longterm care leads to psychological strain, some studies have shown parents of older children with autism to have higher levels of psychological well-being than parents of younger children, implying adaptation to the caregiving role over time. For instance, Fitzgerald, Birkbeck, and Matthews (2002) reported that having an older child with autism (mean age = 15.84 years) is associated with better maternal mental health and less caregiving burden in comparison with having a younger child (mean age = 10.53 years).…”
Section: Age Of Child and Maternal Well-beingmentioning
confidence: 99%
“…An American quantitative study by Bookwala (2009) 52 may explain this difference. With reference to Lawton et al (2000) and Townsend et al (1989), Bookwala proposed that two competing models in the literature of caregiving exist, namely the wear-and-tear model (connected to negative experience and care burden that erodes caregivers' resources and wellbeing) and the adaptation model (which suggests that negative experience appears at the beginning of the caregiving responsibility and then improvement occurs up to baseline levels). The aim of the study was to test the hy-51 In Dunér's (2010) study, 16 family caregivers were interviewed about their experience of giving care.…”
Section: Literature Based On Empiricalmentioning
confidence: 99%
“…This section is based on those articles. Townsend et al (1989) The theory of doing the best I can: Brown et al (2007) Stress process model: Pearlin et al (1990) …”
mentioning
confidence: 99%